If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -2 = 8y + -1y Reorder the terms: -2 + 8y = 8y + -1y Combine like terms: 8y + -1y = 7y -2 + 8y = 7y Solving -2 + 8y = 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -2 + 8y + -7y = 7y + -7y Combine like terms: 8y + -7y = 1y -2 + 1y = 7y + -7y Combine like terms: 7y + -7y = 0 -2 + 1y = 0 Add '2' to each side of the equation. -2 + 2 + 1y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 1y = 0 + 2 1y = 0 + 2 Combine like terms: 0 + 2 = 2 1y = 2 Divide each side by '1'. y = 2 Simplifying y = 2
| f(x)=0.75(x-5) | | -6f-5=-10 | | X^2=1/3x | | 80c+-2c=-59 | | log1/2^(x-3)=-4 | | .40+.10=.50(n+4) | | .40+.10=.50(n+4) | | -5-4x+7x=-8 | | 52=(4+y)-22 | | .40+.10=.50(n+4) | | 2/3(12)=1 | | 2/3(12)=1 | | 2/3(12)=1 | | 5(9-7)=25 | | -5-4x+7x=-8 | | 81/27•6-2 | | -3(a+1)-3=7 | | 6x+10-2x=2x+6 | | .006s=.18 | | x^2-15x+70=0 | | -7x+40=-2x+5 | | -14:23=2/7-1/7x | | 4y-1a=5a+6(3-1y) | | 9x=7+2 | | 7n-32=-32+8n-1n | | 4.5x+28=-10 | | 3x+2g=12 | | N/2-7=-6 | | 4/5(3x-5)=45 | | 14b^2-29b-15=0 | | 4/x=20/75 | | 1.5+.3r=-4.2 |